Amino Acid Composition, Volatile Compounds and Bioavailability of Biocalcium Powders from Salmon Frame as Affected by Pretreatment. Issue 7 (9th August 2019) - Idowu, Anthony Temitope; Benjakul, Soottawat; Sae-Leaw, Thanasak; Sookchoo, Pornsatit; Kishimura, Hideki; Suzuki, Nobuo; Kitani, Yoichiro
ABSTRACT: Biocalcium powders, Bio-cal-H, and Bio-cal-A, obtained from non-alkaline treated and alkaline treated salmon frame were characterized. Glycine was the dominant amino acid (216.45–321.80 mg/g), followed by glutamic acid (102.52–110.38 mg/g), proline (72.96–96.10 mg/g), and hydroxyproline (72.98–83.75 mg/g) in both biocalcium powders. Bio-cal-H possessed a high abundance of volatile compounds such as 2-propanone, acetonitrile, and 2-butanone than Bio-cal-A. Bio-cal-A had a higher solubility in in vitro simulated gastrointestinal tract than Bio-cal-H and CaCO3 ( P < .05). However, transportation of calcium across Caco-2 cell monolayer of Bio-cal-H was higher than Bio-cal-A and CaCO3 ( P < .05). Overall, biocalcium could serve as a promising source of calcium supplementation.